Assessment of the Characteristics and Clinical Outcomes of Un-Booked Obstetric Patients at Tertiary Care Hospital of Southern Punjab: Clinical Outcomes of Un-Booked Obstetric Patients at Southern Punjab Hospital - Khan, Umber Imtiaz; Uzma, Syeda; Shaheen, Zubaida; Ghaffar, Sadia; Mumtaz, Faria; Jabeen, Syeda Surayya (Pakistan Journal of Health Sciences, 2024)
Un-booked obstetric patients often lack adequate antenatal care, leading to increased risks of maternal and neonatal complications. Understanding the characteristics and clinical outcomes in this population is essential to improve healthcare delivery and reduce disparities Objectives: To analyze the characteristics and clinical outcomes of un-booked obstetric patients presented at Tertiary Care Hospital in Rahim Yar Khan. Methods: This cross-sectional study analyzed the outcomes of 384 un-booked obstetric patients presented at the Department of Obstetrics and Gynecology in a Tertiary Care Hospital, between July 2022 to June 2023 aged 18-35 years. obstetric outcomes including the type of labour, mode of delivery, premature rupture of membranes and postpartum hemorrhage were studied in enrolled patients. Results: The mean age and mean gestational age of un-booked obstetric patients were 27.08 ± 4.59 years and 36.31 ± 4.18 weeks respectively. Vaginal deliveries were 257 (66.9%) and C-section was performed in 127 (33.1%) patients. Regarding the type of labor, term and preterm deliveries were 312 (81.3%) and 72 (18.7%), similarly premature rupture of membranes and postpartum hemorrhage were noted in 42 (10.9%) patients and 30 (7.8%) patients. Conclusion: It was concluded that un-booked obstetric patients primarily experienced vaginal deliveries with a low incidence of complications such as premature rupture of membranes and postpartum hemorrhage. Parity significantly influenced delivery and labor outcomes, highlighting the need for targeted antenatal care for high-risk groups such as primiparous and nulliparous women. These findings emphasize the importance of improving access to antenatal care to optimize maternal and neonatal outcomes.